Review on Thermophysical Properties and Corrosion Performance of Molten Salt in High Temperature Thermal Energy Storage. Issue 5 (April 2020) - Song, Xiaoyun; Zhang, Gaoqun; Tan, Hui; Chang, Liang; Cai, Linhai; Xu, Guizhi; Deng, Zhanfeng; Han, Zhibo
Abstract: Molten salt is a type of material for high temperature thermal energy storage. The thermophysical property, thermostability, and corrosion performance of molten salt are the main points of interest in thermal energy storage field. How to further broaden the usage temperature range of molten salt, develop more molten salts with low melting points, and optimize the thermal conductivity and viscosity of materials has been widely concerned by researchers. Recently, thermal storage technology of molten salt has been applied to the field of concentrating solar power. The thermophysical property, and corrosive performance of molten salt are very important for the large-scale preparation and application of molten salt materials. Based on the classification of molten salt materials, this paper reviews the thermophysical properties of some common molten salts (carbonate, chloride, nitrate, polybasic salt, etc.), and summarizes the current research progress of improving its thermophysical properties. Moreover, the corrosive performance of several types of commonly used molten salts in thermal energy storage applications is analyzed. Besides, some corrosion protection technologies are proposed according to the current application of molten salt and the corrosion mechanism. Finally, the development trend of the application of molten salt in the field of heat storage is prospected.